(3GdceGd aj eYQaI GdQLGds - (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3jHOC HJQLeI NGdO Hf jRjO s
(3BNQgG (B:s
(3hjfJgi HJQLeI YHjO Gddg Hf Sgd CHh djdi s
(3GdfSNI HgG MhGTs
(3ef fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
Keywords: (3GdJGQjNs